H. ZAINAL ARIFIN ABBAS'S CONTRIBUTION IN THE FIELD OF EDUCATION - Arsyad, Junaidi; Nursalimah, Nursalimah; Mukti, Abd; Ritonga, Maisaroh (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: In North Sumatra, one of the figures who is viewed as a ulama, all the more exactly a scholarly mastermind who gave information and contributed significantly to society, was H. Zainal Arifin Abbas (1912-1979M), one of the ulama who been able to tackle the issues of the ummah during his time. Purpose: This research discusses about the contribution of H. Zainal Arifin Abbas of education in North Sumatra. This issue should be explored for a few significant reasons, to be specific exploration on Abbas can uncover how the historical backdrop of training in North Sumatra created, by looking at the contributions of H. Zainal Arifin Abbas can help in forming more powerful instructive methodologies in view of the encounters and fruitful drives of past figures, this research can evaluate the impact of policies, programs or methods introduced by him future improvement and advancement of education. Method: This research is a type of qualitative research with a character study approach. Data validity techniques are carried out with a degree of trust (credibility) and dependability by auditing research data. The data analysis used in this research is the character study method. Result: The results of this research are in general the contribution of H. Zainal Arifin Abbas in the field of education, to be specific starting the foundation of instructive organizations like Madrasah Arabiyah School (El Hidayah) Kampung Lalang, Al-Ittihadiyah Teladan Islamic Establishment Medan and Taman Siswa Binjai, he is likewise a savvy teacher , scholastic authorities at colleges, example, UISU and Al-Ittihadiyah and produce composed works that become obligatory references in instructive organizations. Conclusion: Therefore, it can be concluded that H. Zainal Arifin Abbas is worthy of being considered a role model due to their substantial contributions, including the production of numerous written works and establishment of educational institutions, aimed at advancing the future of education.